Problematika Kewenangan Pengadilan Tata Usaha Negara Dalam Pengujian Unsur Penyalahgunaan Wewenang - Ihfan, Awaludin Nur (Media Iuris, 2024)
AbstractThe Administrative Court has the authority to examine the elements of abuse of authority based on Article 21 of Government Administration Act in conjunction with Supreme Court Regulation (Perma) 4/2015. This authority has several problems such as the vagueness of the limitation of authority in Article 2 of Perma 4/2015 and the legal vacuum of the application period. The purpose of this research is to provide a prescription to answer some of these problems. The type of research uses normative legal research with a statutory approach, case approach, and conceptual approach. The results of the analysis show that the phrase before the criminal process in Article 2 paragraph (1) can be interpreted as before the investigation process because it is the earliest stage of the criminal process under the Criminal Procedure Code, but the provision must still be reformulated because it results in dualism of authority and contradicts the purpose of the establishment of the abuse of authority element test. Meanwhile, the phrase APIP supervision results in Article 2 paragraph (2) must be interpreted as the results of supervision both in the form of Regular and Specific Purpose in order to provide protection and equality before the law for parties harmed by both forms of supervision. Regarding the legal vacuum of the application deadline, it cannot directly apply the provisions of the lawsuit deadline in the State Administrative Court Law because of the difference in concepts and paradigms between the two. It is better to conduct a more comprehensive study in advance in order to formulate the provisions of the grace period for testing the elements of abuse of authority with legal certainty and justice.Keywords: Authority; State Administrative Court; Examining Elements of Abuse of Authority. AbstrakPTUN memiliki kewenangan untuk melakukan pengujian unsur penyalahgunaan wewenang berdasarkan Pasal 21 UUAP juncto Perma 4/2015. Kewenangan tersebut memiliki beberapa problematika seperti kekaburan batasan kewenangan dalam Pasal 2 Perma 4/2015 serta kekosongan hukum tenggang waktu permohonan. Tujuan penelitian ini adalah untuk memberikan preskripsi guna menjawab beberapa problematika tersebut. Jenis penelitian menggunakan penelitian hukum normatif dengan pendekatan perundang-undangan, pendekatan kasus, dan pendekatan konseptual. Hasil analisis menunjukkan bahwa frasa sebelum adanya proses pidana dalam Pasal 2 ayat (1) dapat dimaknai sebagai sebelum proses penyelidikan karena merupakan tahap proses pidana paling awal berdasarkan KUHAP, tetapi ketentuan tersebut tetap harus direformulasi karena mengakibatkan dualisme kewenangan serta bertentangan dengan tujuan dibentuknya pengujian unsur penyalahgunaan wewenang. Sedangkan frasa hasil pengawasan APIP dalam Pasal 2 ayat (2) harus dimaknai sebagai hasil pengawasan baik dalam bentuk Reguler maupun Tujuan Tertentu agar dapat memberikan perlindungan serta persamaan dihadapan hukum bagi pihak yang dirugikan oleh kedua bentuk pengawasan tersebut. Terkait kekosongan hukum tenggang waktu permohonan tidak bisa secara langsung menerapkan ketentuan tenggang waktu gugatan dalam UU PTUN karena perbedaan konsep dan paradigma antara keduanya. Sebaiknya dilakukan pengkajian yang lebih komprehensif terlebih dahulu guna merumuskan ketentuan tenggang waktu permohonan pengujian unsur penyalahgunaan wewenang yang berkepastian hukum dan berkeadilan.Kata Kunci: Kewenangan; Pengadilan Tata Usaha Negara; Pengujian Unsur Penyalahgunaan Wewenang.